Lattice Boltzmann modeling of droplet condensation on superhydrophobic nanoarrays - Zhang, Qingyu (Langmuir : the ACS journal of surfaces and colloids, 2014)
Droplet nucleation and growth on superhydrophobic nanoarrays is simulated by employing a multiphase, multicomponent lattice Boltzmann (LB) model. Three typical preferential nucleation modes of condensate droplets are observed through LB simulations with various geometrical parameters of nanoarrays, which are found to influence the wetting properties of nanostructured surfaces significantly. The droplets nucleated at the top of posts (top nucleation) or in the upside interpost space of nanoarrays (side nucleation) will generate a nonwetting Cassie state, while the ones nucleated at the bottom corners between the posts of nanoarrays (bottom nucleation) produce a wetting Wenzel state. The simulated time evolutions of droplet pressures at different locations are analyzed, which offers insight into the underlying physics governing the motion of droplets growing from different nucleation modes. It is demonstrated that the nanostructures with taller posts and a high ratio of post height to interpost space (H/S) are beneficial to produce the top- and side-nucleation modes. The simulated wetting states of condensate droplets on the nanostructures, having various geometrical configurations, compare reasonably well with experimental observations. The established relationship between the geometrical parameters of nanoarrays and the preferential nucleation modes of condensate droplets provides guidance for the design of nanoarrays with desirable anticondensation superhydrophobic properties